Effect of Low Level Laser Application at the End of Surgery to Reduce Pain after Tonsillectomy in Adults - Aghamohammadi, Dawood; Eidi, Mohammad; Lotfi, Alireza; Hosseinzadeh, Hamzeh; Movasaghi, Reza; Motighini, Negar; Bouraima, Stephane Ayoub (Journal of Lasers in Medical Sciences, 2013)
Introduction: Tonsillectomy is among commonest otorhinolaryngologic surgeries. Many methods have been used to control post surgical pain, but despite it, pain is still one of the problems related to this operation. Recently, due to the non invasiveness of low level lasers, this modality has attracted attention. The purpose of this study is to evaluate the effects of low level laser irradiation at the end of surgery on reduction of pain after tonsillectomy in adults. Methods: In a clinical trial, 60 adult patients, candidates for tonsillectomy were randomly assigned to two groups, A and B, and both groups were anesthetized similarly by the same technique. At the end of surgery, in the case group, the tonsils’ bed were irradiated by infrared laser with 980nm wavelength, 100Hz, 4J/cm2 from the infra mandibular angle. In the controlgroup, the tonsils’ bed had laser therapy with a turned off probe. Follow ing laser treatment, the patients were reversed and extubated and consciousness achieved, pain and odynophagia were assessed at 2, 4, 6, 8, 12 and 24h post surgery based on visual analog scale for pain (VAS) and analgesic consumption. Results: In the laser group frequency of patients with pain sensation in each evaluated hour was lower than in the control group. The amount of pain decrease and analgesic consumption reduction was significantly higher in patients who received laser (P=0.01). Conclusion: Based on the results of this study, use of low level lasers is effective in reducing tonsillectomy post surgical pain in adults.